The construction of web applications model in online automated universities' students matching system / Suhana Mohd Jamil - Mohd Jamil, Suhana (2005)
Many web applications are implemented without any formal design approaches and constructed mainly in an ad hoc approach. There is no rigorous, systematic approach, and most current Web application development and management practices rely on the knowledge and experience of individual developers. Furthermore, modeling approaches in web application model often neglect navigation structure. This research aims to construct a Web Application Model for Online Automated Universities' Students Matching System. It discusses several hypermedia design methods. Apart from that, the most suitable hypermedia design model was chosen in order to construct Web Application Model for Online Automated Universities' Students Matching System and takes into account the navigation structure of the system. The model consists of conceptual model, navigation model and presentational model.